CONTRIBUTION POLITICAL ENVIRONMENT IN SUPPORTING RESILIENCE FOOD IN AREA TAHURA WAN ABDUL RAHMAN REGISTER 19 GUNUNG BETUNG - LAMPUNG PROVINCE - Pitojo Budiono; Himawan Indradjat; Eny Puspasari; Kheynad (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Study This study contribution political environment in support resilience food in Park area Forest Raya (Tahura) Wan Abdul Rahman Register 19 Mountain Betung, Province Lampung. An area of 22,240 Ha This face challenge complex Where 86% its territory has inhabited and managed by public local from 47 government area. Study use method qualitative and quantitative simple with sample 30 respondents from Community Source Great Which consists of out of 10 member group farmer, 10 worker public non-members group, And 10 person divided to 5 manager Tahura WAR And 5 apparatus village/sub-district. Results study show that community perspective outskirts forest Still very oriented on increased income without considering condition land. Group farmer generally No realize that perspective politics and government still attached although his status as cultivator land. Political environment still considered blurry by farmer And tend ignore perspective political And government. This research give contribution to understanding dynamics political environment in context food security in conservation areas.